Presence of chromatoid bodies in the Rhodnius genus detected by cytochemical analysis - Alevi, K. C. C. [UNESP]; Castro, N. F. C. [UNESP]; Oliveira, J. [UNESP]; Rosa, J. A. [UNESP]; Azeredo-Oliveira, M. T. V. [UNESP] (Funpec-editora, 2016)
In addition to the epidemiological importance regarding the transmission of Chagas disease, triatomines are also important biological models for cellular studies, because they have holocentric chromosomes, post-reductional meiosis for sex chromosomes, and nucleolar persistence. Although the nucleolus is present during spermiogenesis, it was suggested that it is inactivated and all transcriptional activity necessary for cell differentiation is supported by the chromatoid body (CB). Thus, considering the importance of CB to triatomine spermatogenesis, this paper aims to analyze the presence of this organelle in the Rhodnius genus. The testicles of five adult R. neglectus and R. prolixus males were analyzed after semifine sections were performed, and the material was subjected to silver ion impregnation. The CB organelle was found in the spermatid of both species. Most CB studies focused on the Triatoma genus. This study described the existence of CB in Rhodnius, confirming thus the importance of this cytoplasmic organelle to spermiogenesis of these insect vectors of Chagas disease.
Keywords: Chromatoid body; Nucleolus; Spermiogenesis